'Ale for an Englishman is a natural drink': the Dutch and the origins of beer brewing in late medieval England. Issue 3 (27th May 2019) - Pajic, Milan
ABSTRACT: It is generally acknowledged that during the Middle Ages, the English focused more on the production of ale and that beer production was brought from continental Europe. Indeed, numerous immigrants from the Low Countries settled in various towns where they introduced and popularised the new drink. However, questions about the beginnings of beer production and the involvement of immigrants in beer brewing remain unanswered. This article aims to establish the exact dating for the introduction of beer and its production, for which scholarly estimates still range from the mid fourteenth to the mid fifteenth centuries. It will also examine the reasons that led beer brewers from the Low Countries to settle in England during the fifteenth century, the period when this industry grew substantially in Holland and Zeeland.